A Rare Case of Athelia in a Crossbred Cow - Rani, R. Uma (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The udder is a very important organ and has economic value in dairy cattle. Though highly vulnerable to various disease conditions, e.g. mastitis, congenital anomalies in the udder are of rare occurrence (Dandale et al., 2013). Congenital abnormalities of the mammary system in cows comprise absence of teats, glands, supernumerary teats and imperforate teats. Absence of teat is extremely rare, but isolated cases in which the teats were only represented by slight eminences have been met with (O’ Connor, 1980). Athelia was reported in buffaloes by Sailendra and Sandhya (1998) and Vidyasagar (2009) and in a Japanese black heifer by Ghanem et al. (2011). In the present paper, a rare case of athelia in a Jersey crossbred cow and its therapeutic management by permanent cessation of lactation is reported.